Mexican Screening Test for Olfactory Dysfunction using Essential Oils (Global Journal of Medical Research, 2023)
Introduction Olfaction is important for us to relate to the environment Approximately 25 of the population over 40 years of age has an olfactory disorder Olfactory alterations have a negative impact on quality of life affecting self-esteem generating depression social isolation and even altering eating habits There are multiple etiologies post-viral traumatic metabolic secondary to medication smoking and alcoholism neurodegenerative diseases among others The tests available to screen for hyposmia include pens and books that give off scents are expensive difficult to access require trained personnel to apply them and have been standardized in populations culturally different from the Mexican population which makes it difficult to detect patients Objectives To create standardize and validate a screening test for olfactory alterations based on essential oils for the Mexican population
Keywords: olfactory disorders; olfactory loss; screening; diagnosis